Quality of life and influencing factors of non-small cell lung cancer patients treated with first-line targeted therapy in Vietnam: A study using the EORTC QLQ-C30 scale - Chinh Van Nguyen; Nhat Huu Nguyen; Linh Dieu Hoang; Huong Thi Thanh Tran; Kiet Tuan Pham Huy (Vietnam Journal of Science, Technology and Engineering, 2025)
A cross-sectional descriptive study was conducted using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) scale to measure the quality of life (QoL) of 310 non-small cell lung cancer (NSCLC) patients with EGFR mutations receiving first-line targeted therapy at the Vietnam National Cancer Hospital from October 2022 to December 2023. A Tobit regression model was employed to identify factors associated with the QoL of NSCLC patients. The global health status of NSCLC patients was rated at 62.88 points, with financial difficulties scoring 51.08 points. Among the functional scales, physical functioning scored the highest at 85.72 points, followed by role functioning (79.57), cognitive functioning (78.66), social functioning (71.72), and emotional functioning, which scored the lowest at 65.83 points. Regarding the symptom scales, insomnia scored the highest at 35.48 points, followed by fatigue (31.33), pain (25.11), diarrhoea (23.33), appetite loss (17.1), and dyspnoea, which scored the lowest at 4.62 points. Factors such as low income, residing in rural areas, and experiencing fatigue symptoms have a detrimental effect on the QoL of NSCLC patients. Improving fatigue symptoms, supporting income for low-income patients, and offering financial assistance, such as providing complimentary bus tickets and meals at the hospital, can alleviate financial strain and prolong the duration of support for NSCLC patients.